INTERNALIZATION OF TRADITIONAL PLAY-BASED ECOLOGICAL AWARENESS IN CHILDREN OF RURAL COMMUNITIES - Akhmad Ghasi Pathollah; Misbahul Munir; Riko Prayogo (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This research aims to explore ecological awareness based on traditional games of children in rural communities. This emerges as a reflective response to the development of communication technology in the form of the internet and gadgets that build new characters in the habits of today's children. Children are familiar with gadgets and spend most of their time in cyberspace, which has implications for awareness that is distant from the real surrounding nature. This in turn leads to a crisis of ecological awareness in future generations of society. This research uses a descriptive qualitative method with a case study type. The data collection techniques used are observation, documentation and depth-interview. In collecting data, this research uses the Miles and Huberman interactive model, namely; data reduction, data presentation, conclusion drawing. In testing the validity of the data, researchers used triangulation, namely source triangulation, method triangulation, peer discussion and member check. This study found a statement that traditional games of rural communities are based on materials in the surrounding nature and these traditional games contribute to building ecological awareness of children in rural communities.